2018
DOI: 10.1039/c8nj03358g
|View full text |Cite
|
Sign up to set email alerts
|

New oxidovanadium(iv) complex with a BIAN ligand: synthesis, structure, redox properties and catalytic activity

Abstract: The combination of a new oxidovanadium(iv) complex1with pyrazine-2-carboxylic acid (PCA; a cocatalyst) affords a catalytic system for the efficient oxidation of saturated hydrocarbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 116 publications
0
31
0
Order By: Relevance
“…A ferromagnetic intermolecular interaction between the molecules in the chains of polymeric oxidovanadium(IV) complexes with tetradentate Schiff base ligands have been found [39]. The IR spectra of the complexes 1-4a show a strong V = O stretching band around 880-890 cm −1 which is typical for linear chain V = O…V = O polymeric structures [34][35][36][37][38][39] This band is significantly blue-shifted in the IR spectra of monomeric oxidovanadium complexes [63][64][65][66]. A ferromagnetic intermolecular interaction between the molecules in the chains of polymeric oxidovanadium(IV) complexes with tetradentate Schiff base ligands have been found [39].…”
Section: Synthesis and Characterization Of Compounds 1-4amentioning
confidence: 92%
See 2 more Smart Citations
“…A ferromagnetic intermolecular interaction between the molecules in the chains of polymeric oxidovanadium(IV) complexes with tetradentate Schiff base ligands have been found [39]. The IR spectra of the complexes 1-4a show a strong V = O stretching band around 880-890 cm −1 which is typical for linear chain V = O…V = O polymeric structures [34][35][36][37][38][39] This band is significantly blue-shifted in the IR spectra of monomeric oxidovanadium complexes [63][64][65][66]. A ferromagnetic intermolecular interaction between the molecules in the chains of polymeric oxidovanadium(IV) complexes with tetradentate Schiff base ligands have been found [39].…”
Section: Synthesis and Characterization Of Compounds 1-4amentioning
confidence: 92%
“…Vanadium trichloride adduct with tetrahydrofuran ([VCl 3 (thf) 3 ]) and vanadium tribromide (VBr 3 ) were used as starting compounds which were oxidized during the reaction in air to give the V = O moiety (Scheme 1). This synthetic procedure was previously applied for the synthesis of other oxidovanadium(IV) complexes with chiral dehydrophenanthroline and diazofluorene ligands as well as with the redox-active bis(N-(2,6-diisopropylphenyl)imino)acenaphthene (dpp-bian) ligand [25,63]. The reactions of the corresponding vanadium precursor and 2,2 -bipyridine (bpy) or 1,10-phenanthroline (phen) in a 1:1 molar ratio resulted in microcrystalline products in yields ranging from moderate to high.…”
Section: Synthesis and Characterization Of Compounds 1-4amentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed model is also in agreement with the experimental data. Gushchin, Kuznetsov, et al recently [84,85] observed high activity among the vanadium complexes shown in Scheme 5 in the oxidation of hydrocarbons with peroxides. The mechanism for the generation of OH radicals is presented in Scheme 6.…”
Section: Oxidation Of Hydrocarbons and Alcohols With Peroxides Catalymentioning
confidence: 96%
“…Machura et al [79] described the oxidation of inert alkanes to alkyl hydroperoxides by H2O2 catalyzed with monomeric oxovanadium(V) complexes of 8-hydroxyquinoline derivatives as noninnocent ligands (Scheme 4). The analogous ligands in complexes with copper or rhenium were used in oxidations by peroxides [80][81][82][83] Gushchin, Kuznetsov, et al recently [84,85] observed high activity among the vanadium complexes shown in Scheme 5 in the oxidation of hydrocarbons with peroxides. The mechanism for the generation of OH radicals is presented in Scheme 6.…”
Section: Oxidation Of Hydrocarbons and Alcohols With Peroxides Catalymentioning
confidence: 99%